An international survey of management of pain and sedation after paediatric cardiac surgery. Issue 1 (5th July 2017) - Zeilmaker-Roest, Gerdien A; Wildschut, Enno D; van Dijk, Monique; Anderson, Brian J; Breatnach, Cormac; Bogers, Ad J J C; Tibboel, Dick
Abstract : Objective: The mainstay of pain treatment after paediatric cardiac surgery is the use of opioids. Current guidelines for its optimal use are based on small, non-randomised clinical trials, and data on the pharmacokinetics (PK) and pharmacodynamics (PD) of opioids are lacking. This study aims at providing an overview of international hospital practices on the treatment of pain and sedation after paediatric cardiac surgery. Design: A multicentre survey study assessed the management of pain and sedation in children aged 0–18 years after cardiac surgery. Setting: Pediatric intensive care units (PICU)of 19 tertiary children's hospitals worldwide were invited to participate. The focus of the survey was on type and dose of analgesic and sedative drugs and the tools used for their pharmacodynamic assessment. Results: Fifteen hospitals (response rate 79%) filled out the survey. Morphine was the primary analgesic in most hospitals, and its doses for continuous infusion ranged from 10 to 60 mcg kg -1 h -1 in children aged 0–36 months. Benzodiazepines were the first choice for sedation, with midazolam used in all study hospitals. Eight hospitals (53%) reported routine use of sedatives with pain treatment. Overall, type and dosing of analgesic and sedative drugs differed substantially between hospitals. All participating hospitals used validated pain and sedation assessment tools. Conclusion: There was a large variation in the type and dosing of drugs employed in the treatment of pain and sedation after paediatric cardiac surgery. As a consequence, there is a need to rationalise pain and sedation management for this vulnerable patient group.